بناء مقياس حب التعليم للبالغين = Developing the love of learning scale for adult students - Deeb Aljaji, Raja Mohamed; Al-Hidabi, Dawood Abdulmalek Yahya; Al-Hammadi, Abdullah Othman (University of Science and Technology - Yemen, 2019)
The study aimed at developing the love of learning scale for adults. The scale consisted of 15 situations to measure three dimensions namely intimacy, passion, and commitment towards learning. The scale was standardized on a sample of 111 university male and female students from the 4th level of the Faculty of Education, Sana'a University, Yemen. The validity and reliability of the scale was (0.81) based on Cronbach' Alpha. The results of the study showed that the level of learning was of average level.